Low Systolic Blood Pressure and Mortality From All Causes and Vascular Diseases Among Older Middle-aged Men: Korean Veterans Health Study - Sang-Wook Yi; Heechoul Ohrr (Korean Society for Preventive Medicine, 2015)
Objectives: Recently, low systolic blood pressure (SBP) was found to be associated with an increased risk of death from vascular diseases in a rural elderly population in Korea. However, evidence on the association between low SBP and vascular diseases is scarce. The aim of this study was to prospectively examine the association between low SBP and mortality from all causes and vascular diseases in older middle-aged Korean men. Methods: From 2004 to 2010, 94 085 Korean Vietnam War veterans were followed-up for deaths. The adjusted hazard ratios (aHR) were calculated using the Cox proportional hazard model. A stratified analysis was conducted by age at enrollment. SBP was self-reported by a postal survey in 2004. Results: Among the participants aged 60 and older, the lowest SBP (<90 mmHg) category had an elevated aHR for mortality from all causes (aHR, 1.9; 95% confidence interval [CI], 1.2 to 3.1) and vascular diseases (International Classification of Disease, 10th revision, I00-I99; aHR, 3.2; 95% CI, 1.2 to 8.4) compared to those with an SBP of 100 to 119 mmHg. Those with an SBP below 80 mmHg (aHR, 4.5; 95% CI, 1.1 to 18.8) and those with an SBP of 80 to 89 mmHg (aHR, 3.1; 95% CI, 0.9 to 10.2) also had an increased risk of vascular mortality, compared to those with an SBP of 90 to 119 mmHg. This association was sustained when excluding the first two years of follow-up or preexisting vascular diseases. In men younger than 60 years, the association of low SBP was weaker than that in those aged 60 years or older. Conclusions: Our findings suggest that low SBP (<90 mmHg) may increase vascular mortality in Korean men aged 60 years or older.